A Semiotic Study of the Annual Reports of PT Bank Central Asia, Tbk Before and During Its Recognition as the Winner of the 2023 Annual Report Award (ARA) - Khoiriyah, robi'atul; Putri, Intan Lifinda Ayuning (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
This study examines the transformation of corporate communication in PT Bank Central Asia Tbk’s annual reports before and after winning the Annual Report Award (ARA) 2023 through a three-stage semiotic approach. Using a qualitative interpretative method and content analysis based in syntax, semantics and pragmatics, the research focuses on narrative text, data visualization, and financial reports from 2022-2024. The results show that narrative structure evolved from passive-descriptive (2022) to active-persuasive and cohesive (2023-2024), with increasingly narrative infographic-visual integration. Semantically, net profit transformed from a recovery symbol (2022) into evidence of digital-ESG transformation success (2023) and a post-award stability marker (2024) . ESG evolved from an administrative supplement to a core corporate identity foundation. Pragmatically, the annual report ‘s communicative function shifed from informative to persuasive-legitimation, with narratives influencing investor and stakeholder perceptions. These findings reinforce the understanding that annual reports act as media for social reality construction and symbolic legitimation instruments. Practical implications emphasize the importance of strategic narratives, persuasive visuals, and  ESG meaning in strengthening reputation and market trust. This study contributes to qualitative accounting and financial communication literature, particularly for  companies seeking symbolic advantage through sustainable reporting.